Socioeconomic Problems of Transformational Period - Lydeka, Zigmas (Ekonomika, 1997)
Obvious transformational changes have become prevalent in the socioeconomic evolution of civilization at the end of the XXth century: former socialist countries have refused a planned economy and have chosen a market economy; developed countries are creating a post-industrial (informed) society; developing countries are shaping industrial-agricultural structures; all countries have to solve global problems. These are several examples of our world transformation affecting both each country’s future and the existence of civilization in general.Quite important, hard to foresee, and sometimes difficult to understand, transformational changes are taking place in the countries of former command economies. The author tried to systematize the present economical and political events, indicating their tendencies to persist, end, or be modified. Every theoretical conclusion was not intended to be illustrated by definite facts. Outlined theoretical statements were made on the basis of Lithuanian economical transformational practice, as well as on similar processes in other countries and those described in scientific literature.The transformational period of the economic system is that particular period when the process of changes of the economic system is occuning (the previous system is being destroyed, and the new system is being built). During this period, neither system usually works well. This period is influenced by an old inert system and a new dynamic one. The situation determines a rather primitive, vulgar, changeable, and temporary transformational periodical economy characterized by lots of mistakes and a stressed ideology.Transformational processes may be natural or artificial. The transformation of economic systems is, therefore, the whole complex of some natural and some artificial processes. The transformational period in Lithuania may, then, be considered as a return to the natural development of the world economy. The article analyzes the problems of the interaction of natural, artificial, economic, and political processes.The duration of the transformational period depends on how quickly the principal parameters of the new economic system are formed. This, of course, may last for some years or several decades. Theoretically, the transformational period may continue long enough if natural evolution is combined with effective outside interference (government regulations), i.e. artificial processes. It is quite clear why political reforms should be well-founded and well-combined with economic reforms, why the priorities of the country’s development should be stated and their takeover and continuity be ensured while the governmental staff changes. Otherwise, the transformational period may extend for a very long time, while economic crisis, social discomfort, and even doubts about the necessity of a market economy rise.The socioeconomic problems of the transformational period considered in the article are:1. The importance of changing the dominate economical tendency based on economic freedom.2. The eagerness to overcome the present economical retardation, to stimulate the speed of economic growth and the attempt approach the level of economy as that of developed countries.These two problems may be called a country’s strategic tasks of the transformational period.Solving these tasks would mean corresponding changes in owning property, in technology, management, consumption, investment, infrastructure, and in the population’s way of thinking. To solve the first problem is to return to the natural mode of world development. To solve the second one is to reach (or at least approach) the world economic level.The author then analyzed the conditions which are essential for a successful solution to the main problems:1. Establishing effective prerequisites for the functioning of a market economy.2. The inevitable costs of the new economy.3. Subjects and their activities.Without the above mentioned conditions, it is impossible to succeed. The sooner the prerequisites for the functioning of a market economy are created, the more significant the problem of stimulating economic growth will be.The second macroeconomic problem requires:1. Chosing a high speed of economic growth.2. Finding and accumulating the necessary resources which are, of course, associated with internal investments and foreign investments.